2016
DOI: 10.1111/nmo.12808
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus‐induced pacemaker activity in interstitial cells of Cajal associated with the deep muscular plexus of the small intestine

Abstract: Substance P changes non-synchronized high frequency flickering or quiescence in ICC-DMP into strong rhythmic calcium transients that are synchronized within the network; they are associated with rhythmic transient depolarizations within the same frequency range. We hypothesize that Substance P, released from nerves, can evoke rhythmicity in ICC-DMP, thereby providing it with potential pacemaker activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In addition, mathematical modeling suggested that ICC-DMP might be involved in generation of the minute rhythm of peristaltic contractions (Huizinga et al, 2015). Furthermore, we proved the concept of ICC-DMP being stimulus-dependent pacemaker cells when we established that Substance P changed non-synchronized high frequency intracellular calcium flickering or quiescence in ICC-DMP into strong rhythmic calcium transients that were synchronized within the network and associated with rhythmic transient depolarizations (Zhu et al, 2016). The cluster-associated depolarizations were facilitated by ICC-DMP and not by the ICC-MP, since ICC-MP driven contractions remained after clusters were abolished; furthermore, the distention-induced minute rhythm is prominent in WWv mice that lack ICC-MP (Huizinga et al, 1998).…”
Section: Icc-dmp As Stimulus-dependent Pacemaker Cellssupporting
confidence: 54%
“…In addition, mathematical modeling suggested that ICC-DMP might be involved in generation of the minute rhythm of peristaltic contractions (Huizinga et al, 2015). Furthermore, we proved the concept of ICC-DMP being stimulus-dependent pacemaker cells when we established that Substance P changed non-synchronized high frequency intracellular calcium flickering or quiescence in ICC-DMP into strong rhythmic calcium transients that were synchronized within the network and associated with rhythmic transient depolarizations (Zhu et al, 2016). The cluster-associated depolarizations were facilitated by ICC-DMP and not by the ICC-MP, since ICC-MP driven contractions remained after clusters were abolished; furthermore, the distention-induced minute rhythm is prominent in WWv mice that lack ICC-MP (Huizinga et al, 1998).…”
Section: Icc-dmp As Stimulus-dependent Pacemaker Cellssupporting
confidence: 54%
“…; Zhu et al . , ). In physiological conditions, a stimulus is most likely to be experienced locally and not to be uniform along the entire intestine.…”
Section: Resultsmentioning
confidence: 99%
“…; Zhu et al . , ). Here, we show that locally increasing slow‐wave frequency has marked effects on motor patterns but does not necessarily increase propulsive activity.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that substance P can evoke the ICC-DMP pacemaker. 43 Potential stimuli are not limited to neurotransmitters; fatty acids such as butyrate and decanoic acid can also evoke the low frequency pacemaker activity, 34 and so can distention. 44 Siegle and Ehrlein's observation that neurotensin can evoke segmentation can be explained by the induction of ICC-DMP pacemaker activity.…”
Section: Discussionmentioning
confidence: 99%